WORD FORMATION IN THE JAKARTA POST ARCHIPELAGO ARTICLE - Aulia, Rara Silvany; Ramadhani, Adinda; Siregar, Anniza Nursyahbani (International Conference on Humanity Education and Society (ICHES), 2024)
The objectives of the study are to determine the types of word formation that appear in archipelago articles and determine which ones are the most dominant. In this research, there are several ways to analyze and find data, including reading data, analyzing words, collecting data, grouping data according to word formation, describing data, and making conclusions. This word formation process is an important from of knowing what the word formation processes are contained in archipelago articles, which many people do not know what the processes are. This study uses a qualitative method. The data used in the form of archipelago articles in the 2023 edition of the Jakarta post is 3 articles. The results of this research found 81 words of word formation. There are 6.17% of acronyms, 3.70% of clipping, 3.70% of orthographic abbreviation, 13.58% of borrowing, 7.40% of compound, 17.28% of backformation, 7.40% of conversion, 40.74% of multiple process then, the type of word formation that is not found in the articles is blending.